Medically Unexplained Symptoms among Adults from Russia: An Assessment using the Patient Health Questionnaire-15 - Alena A. Zolotareva (Psychology in Russia: State of Art, 2023)
Background. The Patient Health Questionnaire-15 (PHQ-15) is one of the most frequently used instruments to measure medically unexplained symptoms in the general population as well as in groups of patients with mental and physical health problems. Objective. This study aimed to examine the psychometric properties of the PHQ-15 in assessing a Russian community sample. Design. A total of 1153 Russian adults age 18 or older participated in this cross-sectional study. They completed the Russian versions of the PHQ-15 and Symptom Check List-90-Revised, SCL-90-R (SCL-90-R). Exploratory and confirmatory factor analyses were used to examine the factor structure of the Russian PHQ-15, and multi-group confirmatory factor analyses were used to test measurement invariance across sex and age. Cronbach’s alpha coefficients and Pearson’s correlation coefficients were used to evaluate the internal reliability and convergent validity of the Russian PHQ-15. Results. Exploratory factor analysis revealed a three-factor solution highlighting pain-fatigue, gastrointestinal, and cardiopulmonary symptoms. Confirmatory factor analysis confirmed a bifactor structure for the Russian PHQ-15 merging general and specific somatic symptoms. A multi-group confirmatory factor analysis showed partial invariance across sex and age. The Russian PHQ-15 demonstrated acceptable Cronbach’s alpha coefficients ranging from 0.72 to 0.75 for specific factors and a good Cronbach’s alpha for the total score (α = 0.85), proving the questionnaire’s internal reliability. Finally, positive correlations between the PHQ-15 and SCL-90-R dimensions, and positive intercorrelations between PHQ-15 specific factors, suggested convergent validity. Conclusion. The Russian PHQ-15 is a reliable and valid instrument for assessing medically unexplained symptoms in the general population. This instrument can be used in diagnostic and counseling settings.